A comparative analysis of news by the English language broadcast and print media in Malaysia - Lee, Siew Tin (Universiti Sains Malaysia, 1982)
Novelists often say that characters in their stories have a way of "coming alive" and taking control of the directions of their plots. Likewise, in the process of analysing the data for this 'academic exercise', new questions and facts have continually emerged from the raw data and thereby determined the ultimate direction which this study has taken. My 'academic exercise' aims at analysing the news given by the English language broadcast and print media in Malaysia. The main reason why I believe such a study is worthwhile is that, the media besides being a mirror of our society, more importantly, influence it , too. Public thinking, discussion and behaviour often hinge on what the media have selected to include in their publications and broadcasts.